2012
DOI: 10.5402/2012/480650
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Chemoembolization: History for More than 30 Years

Abstract: Transcatheter arterial chemoembolization (TACE) is a minimally invasive technique to treat liver tumors, particularly hepatocellular carcinoma (HCC). TACE was used in early times to treat liver tumor patients with emergencies caused by symptomatic humoral hypercalcemia and develops gradually from the procedures of diagnostic angiography and transcatheter injection of agents and is in particular performed in the treatment of HCC. Since the beginning of this century, TACE has been used extensively in the palliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 59 publications
(79 reference statements)
0
55
0
4
Order By: Relevance
“…TACE was performed according to the traditional method. 17 Chemotherapeutic agents, 100-mg oxaliplatin and/or 1000-mg fluorouracil glycosides were infused into feeding arteries of the tumor; subsequently, 5-to 20-mL Lipiodol mixed with 30-mg epirubucin was infused into the feeding arteries at a rate of 1 mL/min until stasis flow in the tumor vascularity was achieved. Repeated TACE operations were performed when residual tumors or new lesions were confirmed in patients with preserved hepatic function.…”
Section: Patientsmentioning
confidence: 99%
“…TACE was performed according to the traditional method. 17 Chemotherapeutic agents, 100-mg oxaliplatin and/or 1000-mg fluorouracil glycosides were infused into feeding arteries of the tumor; subsequently, 5-to 20-mL Lipiodol mixed with 30-mg epirubucin was infused into the feeding arteries at a rate of 1 mL/min until stasis flow in the tumor vascularity was achieved. Repeated TACE operations were performed when residual tumors or new lesions were confirmed in patients with preserved hepatic function.…”
Section: Patientsmentioning
confidence: 99%
“…Conventional TACE typically involves delivering a mixture of the chemotherapy in Lipiodol® (ethiodized poppyseed oil) with follow-up infusion of embolic particles in an effort to locally contain the chemotherapy by avoiding perfusion-mediated wash-out [47]. However, recent studies have shown that after TACE procedures, the creation of ischemic conditions at the tumor promotes a pro-angiogenic response in order to allow the tumor to continue to thrive.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TACE has been considered to be a treatment of first choice for patients with intermediate-advanced HCC who are not suitable candidates for surgical interventions (3)(4)(5). TACE is minimally invasive, may be performed repeatedly, causes little damage to the liver in most patients, has few complications, and is associated with a short duration of hospital stay (6,7).…”
Section: Introductionmentioning
confidence: 99%